2006
DOI: 10.1115/1.2359478
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mechanical Efficiency of Parallel-Axis Gear Pairs

Abstract: A computational model is proposed for the prediction of friction-related mechanical efficiency losses of parallel-axis gear pairs. The model incorporates a gear load distribution model, a friction model, and a mechanical efficiency formulation to predict the instantaneous mechanical efficiency of a gear pair under typical operating, surface, and lubrication conditions. The friction model uses a new friction coefficient formula obtained by using a validated non-Newtonian thermal elastohydrodynamic lubrication (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
242
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(254 citation statements)
references
References 28 publications
10
242
0
2
Order By: Relevance
“…The drivetrain is another component of automobiles that is vital to fuel economy. The efficiency of gear systems has recently become an important research area as the automotive industry has sought ways to improve fleet fuel economies and reduce pollutant emissions to meet increasingly stringent regulations [11]. Recent work has shown that the efficiency of gear systems is due to several factors including the surface roughness of the mating surfaces, assembly errors (e.g.…”
Section: Effect Of Manufacturing Precision On Operational Efficiencymentioning
confidence: 99%
“…The drivetrain is another component of automobiles that is vital to fuel economy. The efficiency of gear systems has recently become an important research area as the automotive industry has sought ways to improve fleet fuel economies and reduce pollutant emissions to meet increasingly stringent regulations [11]. Recent work has shown that the efficiency of gear systems is due to several factors including the surface roughness of the mating surfaces, assembly errors (e.g.…”
Section: Effect Of Manufacturing Precision On Operational Efficiencymentioning
confidence: 99%
“…Another method is the use of Elastohydrodynamic Lubricant (EHL) model to determine the accurate friction coefficient. The samples of researches in this group are the works of Xu et al [11] and Diab et al [12]. Although the method base on the EHL model seems to give the satisfy results, it consumes large computational time and is still not suitable for practical application.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no standards so far concerning the energy efficiency and measurement procedures for these transmissions. Literature concerning the energy efficiency of gearboxes is limited to models describing the energy behavior of certain components of a gearbox such as gear pairs [5], [6] or the behavior of lubrication [7]. However, as emphasized by recent standards [8], [9] a total system approach is needed to maximize the overall efficieny.…”
Section: Introductionmentioning
confidence: 99%